2017
DOI: 10.1371/journal.pone.0170463
|View full text |Cite
|
Sign up to set email alerts
|

κ-opioid receptor is involved in the cardioprotection induced by exercise training

Abstract: The present study was designed to test the hypothesis that exercise training elicited a cardioprotective effect against ischemia and reperfusion (I/R) via the κ-opioid receptor (κ-OR)-mediated signaling pathway. Rats were randomly divided into four groups: the control group, the moderate intensity exercise (ME) group, the high intensity exercise (HE) group, and the acute exercise (AE) group. For the exercise training protocols, the rats were subjected to one week of adaptive treadmill training, while from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It is shown that administration of KOR agonists can improve cardiac performance after myocardial infarction due to increased expression of myocardial haem oxygenase through the activity of PI3K/Akt signalling pathway [55 ]. The modulatory effect of KOR agonist on Akt signalling pathway has been approved in other contexts [56, 57 ]. Interestingly, the cross‐talks between GSK3 (one of the downstream mediators of Wnt signalling pathway), Akt, and KOR agonists have been shown in cardiac protection induced by remote electro‐stimulation [58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that administration of KOR agonists can improve cardiac performance after myocardial infarction due to increased expression of myocardial haem oxygenase through the activity of PI3K/Akt signalling pathway [55 ]. The modulatory effect of KOR agonist on Akt signalling pathway has been approved in other contexts [56, 57 ]. Interestingly, the cross‐talks between GSK3 (one of the downstream mediators of Wnt signalling pathway), Akt, and KOR agonists have been shown in cardiac protection induced by remote electro‐stimulation [58 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a selective agonist of κ-OR, U50,488H can improve hemodynamics and vascular endothelial function and reverse vascular remodeling by activating cardiovascular κ-OR [ 28 30 ]. Previous studies have confirmed that a higher dose of U50,488H significantly prevented the myocardial ischemia and reperfusion (I/R) injury-induced increase in myocardial lipid peroxidation and depletion of myocardial antioxidants and that κ-OR stimulation exerts a protective effect on vascular endothelium [ 31 , 32 ]. However, the impact of κ-OR stimulation on vascular remodeling during VC remains elusive.…”
Section: Introductionmentioning
confidence: 99%